Pengaruh Audit Tenure, Opini Auditor, dan Reputasi Kantor Akuntan Publik terhadap Audit Report Lag - Yulianingtias, Karina Surya; Triyuwono, Iwan (Universitas Prasetiya Mulya, 2024)
This research aims to examine the influence of audit tenure, auditor opinion and reputation of the Public Accounting Firm as independent variables on audit report lag as a dependent variable based on auditing theory. This research employs quantitative research. This research uses purposive sampling sample selection techniques and uses multiple linear regression analyzed with SPSS 29 as an analyzing tool. The sample used in this research is secondary data in the form of financial reports and annual reports totaling 245 sample data consisting of 83 companies in the Consumer Cyclicals Sector that have met the criteria in the form of companies listed on the Indonesia Stock Exchange (IDX) during the 2020-2022 financial reporting period with complete report data. The research results show that audit tenure and Public Accounting Firm reputation cannot influence audit report lag, while audit opinion has a negative influence on audit report lag. Simultaneously, audit tenure, auditor opinion, and Public Accounting Firm reputation influence the audit report lag negatively.